2011
DOI: 10.1007/s10457-011-9375-6
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Mediterranean oak woodlands: understorey dynamics under different shrub management

Abstract: The effect of experimental disturbances on the dynamics of a shrub community was studied on a'Montado' ecosystem, in southern Portugal. The evolution of the community physiognomy, composition and diversity were monitored after shrub clearing followed by biomass removal, deposition on soil surface and incorporation with the soil, over a 9-year period. Maximum shrub density was recorded in the first year after the disturbances, excepting in mulched plots which showed the greatest number of individuals 1 year lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…This agrees with our results, where short periods between clearings would inhibit the regeneration of trees, since mechanical clearing is a non-selective tool that destroys most seedlings (Arosa et al, 2015), thus the absence of immature trees directly affects negatively the population of adult trees. According to our long term results, we assume that extending shrub clearing for longer periods would benefit natural regeneration, which is in agreement with other short term studies (Canteiro et al, 2011;Godinho et al, 2014;Simões et al, 2016). In fact, other authors' conclusions suggest maintaining shrub cover for a period between 7 and 12 years to help cork oak regeneration and promote tree nursery and soil rehabilitation.…”
Section: Main Limitations To Regenerationsupporting
confidence: 92%
See 2 more Smart Citations
“…This agrees with our results, where short periods between clearings would inhibit the regeneration of trees, since mechanical clearing is a non-selective tool that destroys most seedlings (Arosa et al, 2015), thus the absence of immature trees directly affects negatively the population of adult trees. According to our long term results, we assume that extending shrub clearing for longer periods would benefit natural regeneration, which is in agreement with other short term studies (Canteiro et al, 2011;Godinho et al, 2014;Simões et al, 2016). In fact, other authors' conclusions suggest maintaining shrub cover for a period between 7 and 12 years to help cork oak regeneration and promote tree nursery and soil rehabilitation.…”
Section: Main Limitations To Regenerationsupporting
confidence: 92%
“…In fact, other authors' conclusions suggest maintaining shrub cover for a period between 7 and 12 years to help cork oak regeneration and promote tree nursery and soil rehabilitation. Conversely, periods longer than 12 years could facilitate fire spread due to the accumulation of dead material (Canteiro et al, 2011). EU programs have only been subsidizing planting young cork oak trees but results obtained by Arosa et al (2015) confirmed that direct seeding (or natural regeneration) of cork oak is a good alternative to facilitate regeneration, because emergence success ranged between 43.5% and 63.9%.…”
Section: Main Limitations To Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant biologists generally dry the leaves and fruits at 60-70 °C, because high temperatures cause decreases in organic compounds (Westerman, 1990). Cornelissen et al (2003) have recommended drying the herbaceous stems at 60 °C for 72 hours or at s 80 °C for 48-72 hours, and extended this recommendation to woody stems. Since maquis societies consists of high-level of leaves and thin material, the temperature of drying was set to 65°C in order to prevent any failures due to high temperature.…”
Section: Experimental Data -Statistical Evaluation -Podaci O Eksperimmentioning
confidence: 99%
“…Its main forest tree species are the cork oak (Quercus suber L.) and the holm oak (Quercus rotundifolia Lam.). For a detailed characterization of this ecosystem, which is known as dehesa in Spain, see, for example, Joffre et al (1999) and Canteiro et al (2011).…”
Section: Determination Of the Energy Potentialmentioning
confidence: 99%